Analytical performance and clinical decision limit of a new release for cardiac troponin I assay. (January 2015) - Moretti, M; Pieretti, B; Sisti, D; Rocchi, MB; Gasperoni, S
Background: Cardiac troponins (cTns) are the 'gold standard' biomarker for the diagnosis and prognosis of acute coronary syndrome. Analytical performance is critical at low concentrations of cTn, and many of the current assays do not meet the guideline requirement of a 10% coefficient of variation (CV) at the 99th percentile concentrations. The aim of the study was to establish if the newly released Access® AccuTnI®+3 (AccuTnI+3) cardiac troponin I assay (Beckman Coulter Inc., Brea, CA, USA) reached this objective. Methods: All AccuTnI+3 assays were performed on UniCel® DxI800 analyzer (Beckman Coulter Inc). Limit of Blank (LoB), Limit of Detection (LoD) and Limit of Quantitation (LoQ) were determined according to Clinical Laboratory Standard Institute EP17-A and EP5-A2 protocols. The 99th percentile upper reference limit (URL) was determined by analysing serum samples from 330 apparently healthy blood donors (260 men, 70 women, age range 18–70 years, median age 36 years). Results: LoB and LoD values were 2.6 and 12 ng/L, respectively. The 10% CV was at 18 ng/L (95% confidence interval [CI] 8–25). The 99th percentile URL was 22 ng/L (95% CI 11–34). Conclusions: The newly released assay has improved low-end analytical performance and reaches the goal of having a total imprecision ≤10% at 99th percentile of a healthy reference population (guideline acceptable). With this assay, it is now possible to utilize the 99th percentile as decision level for myocardial injury detection.